Internal Control System Of Cash Receiving And Cash Expenditure In Bimbingan Belajar Primagama Tanjung morawa - Khanti Listya Listya; Sri Liniarti; Rizky Surya Andhayani Nasution (Institute of Computer Science (IOCS), 2022)
Large companies usually have good internal controls, while small companies, SMEs, and franchises typically ignore the importance of internal control. One of the business units with a small income volume is tutoring. Primagama is one of the most significant national mentors in Indonesia. Components of internal control consist of an integrated Prima Edu system, auditor participation, operating management style, and organizational structure. Auditor role in auditing operational financial statements and monitoring effectiveness control internals. The operating management style at Primagama Tanjung Morawa is a decentralized management operating style. The organizational structure is used to separate responsibilities and authorities explicitly in each section to prevent fraud in carrying out its functions. The internal control of cash receipts carried out at Primagama Tanjung Morawa has been going well. Still, two elements are not following the theory of internal control, according to Mulyadi. Overall, it is good because there is already a separation of functions in cash receipts and virtual accounts when students deposit tutoring fees. Internal control of cash expenditure carried out at Primagama Tanjung Morawa is not following the theory of internal control of cash dexpenditure according to Mulyadi.